GENDER REPRESENTATION IN TELEVISION ADVERTISING: A CASE STUDY OF COSMETIC PRODUCTS - Geltri Sutra Purba; Dela Sarifa Manurung; Gracya Natalia Sibarani; Hanna Ulina Christine Panggabean (INJOSEDU: International Journal of Social and Education, 2025)
This study explores the representation of gender in television advertisements for cosmetic products, focusing on the linguistic and visual elements used to construct gender norms and stereotypes. Through a discourse analysis approach, advertisements targeting both women and men are analyzed to uncover the underlying messages conveyed regarding beauty standards, masculinity, and femininity. The findings reveal a reinforcement of traditional gender stereotypes, with advertisements for women emphasizing physical appearance and youthfulness, while those for men highlight strength and dominance. Despite some attempts to challenge these stereotypes, such efforts often remain superficial. The implications of these representations for societal perceptions of gender and the role of consumers in demanding more inclusive and diverse portrayals are discussed. The study highlights the importance of critical discourse analysis in understanding how gender is represented in media and the need for fairer and more inclusive gender representation in advertising to create a more equitable and diverse media landscape.